Comparative evaluation of the effectiveness of video modeling, mobile app (Little Lovely Dentist), and animated video modeling technique in the management of dental anxiety in children: A randomized clinical study - Manasa Chinthala; P. V. Ravindranath Reddy; Aruna Kumari Ganapathi; Vem Preethi; Kodali Srija (Journal of Indian Society of Pedodontics and Preventive Dentistry)
Background: Dental anxiety is one of the most common problems associated with children, as observed in the dental office. Dental treatments for children are focused on patient comfort and anxiety reduction in clinical settings employing behavior guidance strategies. Aim: To compare and evaluate the effectiveness of three different behavioral modification techniques (video modeling, mobile apps, and animated videos) in alleviating dental anxiety in children. Methodology: A total of 90 children aged 5–10 years were randomly divided into three groups, Group 1: Video modeling, Group 2: Animated videos (Roogies), and Group 3: Smartphone dental app (Little Lovely Dentist). Later, all children underwent noninvasive dental procedures, including oral prophylaxis, restorations, and sealant application. Children’s anxiety was assessed objectively through pulse rates and subjectively using an RMS pictorial scale at three intervals. Data were analyzed using SPSS version 22, with P < 0.05 considered as statistically significant. Results: There was a significant reduction in anxiety scores among all children. In the intergroup comparison, there was a statistically significant differences in pulse rates and RMS scores between the three groups before, during, and after dental treatment (P < 0.05). Intragroup comparisons showed significant differences in pulse rates and anxiety scores in groups 2 and 3 (P < 0.05), while RMS scores showed significant differences in all groups (P < 0.05). Conclusion: Children with dental anxiety can benefit from behavior guidance techniques such as video modeling, Roogies, and the Little Lovely Dentist app. The Little Lovely Dentist app was found to be an effective method for alleviating dental anxiety during noninvasive dental procedures.